2018
DOI: 10.1016/j.eplepsyres.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis switching and outcomes in a cohort of patients with potential epilepsy with myoclonic-atonic seizures

Abstract: INTRODUCTION: There is overlap in the electroclinical features of many childhood epilepsy syndromes, especially those presenting with multiple seizure types, such as epilepsy with myoclonic-atonic seizures (EMAS) and Lennox-Gastaut syndrome (LGS). This study aimed to determine the frequency of diagnosis switching and the factors influencing epilepsy syndrome diagnosis in a cohort of children with possible EMAS, as well as to explore the relationship between epilepsy syndromes diagnoses, key electroclinical fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 19 publications
(35 reference statements)
1
18
1
Order By: Relevance
“…Although the most frequent seizure types in MAE are as expected (myoclonic atonic or atonic seizure, 100%; GTCS, 72.7%; and myoclonic seizures, 68.2%), 3,5,6,41 a minority of MAE patients have focal seizures, some (6.9%) with additional focal epileptiform activity on EEG. Focal EEG features have been reported in up to 39% of MAE cohorts 40 and have been proposed as a marker of poor prognosis in MAE 42 . However, we were not able to confirm this hypothesis in this cohort, as two of seven patients with focal EEG abnormalities achieved seizure remission, compared to 22 of 70 patients without focal abnormalities.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Although the most frequent seizure types in MAE are as expected (myoclonic atonic or atonic seizure, 100%; GTCS, 72.7%; and myoclonic seizures, 68.2%), 3,5,6,41 a minority of MAE patients have focal seizures, some (6.9%) with additional focal epileptiform activity on EEG. Focal EEG features have been reported in up to 39% of MAE cohorts 40 and have been proposed as a marker of poor prognosis in MAE 42 . However, we were not able to confirm this hypothesis in this cohort, as two of seven patients with focal EEG abnormalities achieved seizure remission, compared to 22 of 70 patients without focal abnormalities.…”
Section: Discussioncontrasting
confidence: 68%
“…For example, antecedent neurodevelopmental impairments and autistic and cognitive deficits are more characteristic of DEE 43 . Moreover, Eschbach et al reported that more than one‐half of a cohort of 77 patients with suspected MAE undergo epilepsy diagnosis switching 40 . However, we believe that the MAE concept remains broadly useful to guide treatment and prognosis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The ratio of patients who achieved seizure‐free status in previous studies has varied, with rates such as 32%, 58%, 67%, and 68%, in studies that used the original definition by Doose, 1,6,32,33 and 38% in studies in which the recent ILAE definition was applied 18 . Because we recruited patients with the aim of conducting gene analysis, it is possible that our study cohort included a higher number of patients with more severe or intractable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used the original seizure semiology proposed by Doose to compare our cohort with those of previous studies. We included patients with tonic seizures or focal/multifocal EEG spikes because tonic seizures have been reported to develop late in the course of cases with an unfavorable outcome, 16,18 and multifocal EEG spikes have been observed in MAE patients 17,18 . We excluded patients with the following diagnoses: benign myoclonic epilepsy in infancy, Dravet syndrome, LennoxGastaut syndrome, atypical childhood epilepsy with centrotemporal spikes, glucose transporter disorders, and progressive myoclonus epilepsies (https://www.epilepsydiagnosis.org).…”
Section: Methodsmentioning
confidence: 99%